Global Food Safety Regulations: A Comparative Analysis of U.S. and International growers´ responses to the Food Safety Modernization Act (FSMA) - Sabillón C., Gina K. (Zamorano: Escuela Agrícola Panamericana, 2025)
Food safety is a relevant issue impacting public health, the economy, and social well-being. Safety Modernization Act (FSMA) has emerged as a crucial regulatory framework for ensuring safety of food internationally. The primary objective was to identify similarities and differences in compliance and the underlying factors influencing the adoption of food safety practices (FSP) among different farming groups. This project explored the comparative responses of U.S. and international farmers to the FSMA's Produce Safety Rule (FSMA-PSR) through a 40-question survey. An analysis of questions related to Food Safety was conducted for this project. The research findings revealed that FSMA-PSR coverage influenced the adoption of FSP, with covered farmers showing higher implementation rates. The income level also played a critical role, with higher-income farmers being more likely to invest in necessary technologies and training to meet regulatory standards. Additionally, while Produce Safety Alliance (PSA) training positively impacted FSP implementation, it was less influential than financial resources. Organic farming practices, although not directly linked to higher safety compliance, showed potential for enhancing food safety, especially when certified. Major barriers to implement FSMA-PSR included money and time for record-keeping, cleaning and sanitation, and personnel training. The study concluded that inclusive policies are necessary to provide equitable access to resources and training, particularly for lower-income farmers, to ensure broad compliance with food safety standards. These insights contributed to the understanding of agricultural food safety, offering valuable recommendations for policymakers and stakeholders in the agricultural sector.